Self-assembled hyaluronic acid nanoparticle suppresses fat accumulation via CD44 in diet-induced obese mice - Lee, Wang Hee; Rho, Jun Gi; Han, Hwa Seung; Kweon, Sohui; Nguyen, Van Quy; Park, Jae Hyung; Kim, Wook (Carbohydrate Polymers, 2020)
Obesity, a major risk factor for type 2 diabetes and cardiovascular diseases, is characterized by an abnormal expansion of adipose tissue. Herein, we investigated the potential of hyaluronic acid nanoparticles (HA-NPs) as therapeutics to treat obesity-related diseases by assessing the in vitro and in vivo effects of HA-NPs on adipogenesis and lipogenesis. Treatment of 3T3-L1 preadipocytes with HA-NPs resulted in a dose-dependent suppression of adipogenesis and lipid accumulation, and decreased the expression of key adipogenic and lipogenic regulators. However, these HA-NPs mediated effects were not observed in 3T3-L1 cells transfected with siRNAs against CD44, a major HA receptor. Further, HA-NP treatment of diet-induced obese (DIO) mice reduced the epididymal fat mass and suppressed the induction of adipogenic and lipogenic regulators, while these effects were attenuated in the CD44-null mice. Thus, our study provides a better understanding of how HA-NP modulates fat accumulation and presents a potential anti-obesity strategy targeting CD44.
Keywords: 3t3-l1 preadipocytes; Abnormal expansion; Adipogenesis; Cardio-vascular disease; Lipid accumulations; Lipogenesis; Obesity; Self assembled nanoparticles; 3T3-L1 Cells; Adipogenesis; Animals; Diet, High-Fat; Hyaluronan Receptors; Hyaluronic Acid; Lipogenesis; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Nanoparticles; Obesity; Adipogenesis; Hyaluronic acid; Lipogenesis; Obesity; Self-assembled nanoparticles